Goalball: uma revisão de literatura - Souza, Luísa Parra Spagnuolo de [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Goalball is a sports modality that was developed especially for the treatment of post World War II soldiers who had some type of vision impairment. Objective: The present work an imsat exploring the basic foundations of this Paralympic sport, as well as presenting a reflection of the modality in the life of the athletes who develop such sport in their day today life. Methods: The research presents the general history of the modality, the performance of Brazil and its post-Olympics expansion in Toronto. It also presents an extension project developed by UNESP of Bauru in partnership with municipal entities. Discussion: It is possible to find in the research the basic rules of goalball, going through the division of classes, the description of the court and equipment, positions, playing time, substitutions, infractions, as well as the organizational cliche of the modality. The concepts of visual impairment are also addressed to research, staked out by different groups. The performance of Brazil is approached trying to highlight the placing of Brazil in the world ranking presenting the rules of classification.

O Goalball é uma modalidade esportiva que foi desenvolvida especialmente para o tratamento de soldados pós II Guerra Mundial que tinham algum tipo de deficiência de visão. Objetivo: O presente trabalho tem como objetivo explorar os fundamentos básicos dessa modalidade paralímpica, bem como apresentar uma reflexão da modalidade na vida dos atletas que desenvolvem tal esporte em seu dia-a-dia. Metodologia: A pesquisa apresenta o histórico geral da modalidade, a performance do Brasil e sua expansão pós olimpíadas de Toronto. Apresenta ainda um projeto de extensão desenvolvido pela UNESP de Bauru em parceria com entidades do município. Discussão: É possível encontrar na pesquisa as regras básicas do goalball, passando pela divisão de classes, a descrição da quadra e equipamentos, posições, tempo de jogo, substituições, infrações, bem como o clico organizacional da modalidade. Os conceitos de deficiência visual também são abordados a pesquisa, estacados por grupos distintos. O desempenho do Brasil é abordado procurando destacar a colocação do Brasil no ranking mundial apresentando as regras de classificação.
Keywords: Paralimpíadas; Pessoas com deficiência visual; Pessoas com deficiência